Alternative splicing of tumour-related Rac1b is regulated by upstream signalling pathways - Gonçalves, Vânia (2011)
The small GTPase Rac1 regulates signalling pathways controlling actin-dependent cell motility as well as gene transcription. An alternative splicing variant Rac1b is overexpressed in a subset of colorectal tumours and cooperates with mutant B-Raf to sustain tumour cell viability. The alternative splicing mechanism regulating Rac1b expression involves two antagonistic splicing factors, ASF/SF2 and SRp20. Using a Rac1 minigene approach and siRNA-mediated depletion, we identified ASF/SF2 as an enhancer of endogenous Rac1b splicing whereas SRp20 acts as a silencer. Inhibition of the PI3-kinase pathway increased protein levels of ASF/SF2 and promoted Rac1b generation. By contrast, depletion of endogenous protein kinase SRPK1 led to decreased Rac1b expression. Together, these data indicate that altered upstream signaling pathways in colorectal cancer cells will target splicing factors that regulate alternative splicing of the small GTPase Rac1.